ANALISIS ARTIKEL TERKAIT PENERAPAN SISTEM BOARDING PASS PADA PELABUHAN DI INDONESIA - Muhammad Khalish Al-Viqri; Dollar Legard G; Miftahul Arzaq (CV. Adiba Aisha Amira, 2023)
This research aims to analyze articles related to the implementation of the boarding pass system at ports in Indonesia. The research was conducted by reviewing related articles published in the period 2018-2023. The method used in this article is a literature study. The results of the analysis of several articles related to the implementation of the boarding pass system at the Port in Indonesia show that the implementation of the boarding pass system has several benefits, such as time efficiency, security, and passenger comfort. However, there are several obstacles in implementing this system, such as the lack of competent human resources (HR) in managing the boarding Pass System and the availability of mini infrastructure.